UPAYA MENUMBUH-KEMBANGKAN MINAT GEMAR BEROLAHRAGA PADA KELOMPOK USIA REMAJA - Sri Mawarti (Jurnal Pendidikan Jasmani Indonesia, 2006)
This paper intends to reveal the effort to grow teenager interest on sport. We include juniorhigh school student as the teen age, a transition age. At this age level, they hunger to searchfor self-identity. At this point, the interest on sport not all of it came from internal interest, thusrequiring a way to grow their interest.Sport that gives fun, joy, and unity can be use as a weapon to encourage teens to do sportactivities. Body contact sports can be use as a channel in search for identity. These sportgive a prestige when the teen capable acquired a satisfactory achievement, thus this sportcan be use as a model to encourage sport activities especially to boys.Keyword: Interest, sports, Teenage.